Bachelor First Year Education Student’s Attitude towards Learning English - Sharma, Lok Raj (International Research Journal of MMC, 2022)
This article examines the bachelor first year education students’ attitude towards learning English. A cross-sectional survey design was adopted to carry out the research study. Five-point Likert scale statement items regarding the attitude towards learning English were administered to the mass of students at three campuses in the academic year 2018-2019 in Makawanpur District of Nepal. Simple random sampling technique was used to select 270 students as respondents out of the population of 277 students for the study by maintaining the confidence level (95%) and the margin of error (1%). The collected data were statistically analyzed by using SPSS. The study revealed that the students had a positive attitude (Median=4) towards learning English, and they “Agreed” with the statement items. The Mann-Whitney U test and the Kruskal- Wallis H test show that all the students from the three campuses had a positive attitude “Agree” towards learning English regardless of their sex (Sig.=.841), religion (Sig.=.470), and age group (Sig.=.753). This article is important for the teachers, the concerned authorities and the parents, because it provides them with information why the students were interested in learning English.